HEALTH INSURANCE, FERTILITY, AND THE WANTEDNESS OF PREGNANCIES: EVIDENCE FROM MASSACHUSETTS. (16th June 2017) - Apostolova‐Mihaylova, Maria; Yelowitz, Aaron
Abstract : Health insurance reform in Massachusetts lowered the cost of both pregnancy (by increased coverage of pregnancy‐related medical events) and pregnancy prevention (by increasing access to reliable contraception). We empirically examine fertility responses and find no overall effect from increased coverage due to the Massachusetts reform. This finding, however, masks substantial heterogeneity. For married women aged 20 to 34—with high latent fertility and pregnancy wantedness—fertility increased by approximately 1%. For unmarried women in the same age range—for whom pregnancies are typically unwanted—fertility declined by 8%. ( JEL I13, I18, J13)